Portraits of the Artist as a Young Woman : Painting and the Novel in France and Britain, 1800-1860 - Wettlaufer, Alexandra (Book collections on Project MUSE., 2011)
This title focuses on a decisive period in the process of professional self-invention and maps out the concrete and symbolic roles played by women painters, real and fictional, in the construction of female artistic identity in the aesthetic and the public spheres. The author examines the diverse and complex ways canonical and non-canonical women painters and novelists - including Anne Bronte, Sydney Owenson, Margaret Gillies, Marceline Desbordes-Valmore, George Sand, and Hortense Haudebourt-Lescot - figured and brought forth the radical image of a female subject representing the world.--Publisher.